Development of a telescopic boom lift for nursing care: design and optimization using a multibody dynamics approach - Makoto IWAMURA (The Japan Society of Mechanical Engineers, 2017)
Recently, several types of nursing care equipment to aid the lifting and transfer of aged persons have been developed. Especially, rotational boom-type care lifts are used widely because of their simplicity and usefulness. However, such lifts sometimes provide a feeling of uneasiness because during lift-up, the center of the human body moves backward relative to the position of the heel. Hence, in this paper, we first propose a telescopic boom-type care lift to approximate the trajectory of the lift-up motion of a human standing up naturally. By using a multibody dynamics approach, we show that the proposed mechanism can achieve nearly natural standing-up motion and requires a smaller force for lift-up than that required by the conventional-type lift. Next, we develop a prototype telescopic boom-type care lift and verify experimentally that the proposed lift can reduce mental and physical burden compared with the conventional lift. To compare mental burden, we conduct a sensory evaluation by administering a questionnaire. To compare physical burden, we estimate muscle activation based on users' electromyographic signals. These results show the effectiveness of the proposed telescopic boom-type lift. Finally, we consider the optimal design of the proposed care lift structure. We propose an algorithm to seek optimal design parameters that minimize the error between the tip trajectory of the lift and the human chest trajectory measured using a motion capture system.